Nurse's Knowledge In Accomplishing Actions And Following Procedures For Post Sectio Caesarea Wound Care - Nurhaida (Institute of Computer Science (IOCS), 2022)
Sectio Caesarea has recently become a trend because it is considered more practical and less painful, so it is not surprising that it has become the second most common obstetric surgery used in Indonesia and abroad. Sectio caesarea surgery is the main choice for medical personnel to save the mother and fetus. World Health Organization or World Health Organization (WHO) the delivery rate with Sectio Caesarea is around 10-15% of all labor processes (WHO, 2015). In Indonesia the delivery rate with Sectio Caesarea reaches 9.8% and in Yogjakarta the prevalence of childbirth with Sectio Caesarea reaches 15% this prevalence is quite high looking at The highest prevalence occurs in Jakarta, which is 19.9% (RISKESDAS, 2014). This research is descriptive in nature, that is, it aims to identify the actions of nurses in adhering to fixed procedures for postoperative wound care for Sectio Caesarea at Martha Friska Pulo Brayan General Hospital in 2018. Using education and experience research variables. The data collected using a questionnaire as many as 10 statements filled out by observing 45 respondents. The data collected is presented in the form of a frequency distribution table and then discussed using the existing literature method. The results of the research that has been done are known that the actions of nurses in complying with fixed procedures for postoperative wound care caesarean section are the majority obedient as many as 40 respondents (88.8%) of 45 respondents. Based on DIII education the majority obeyed as many as 25 respondents (55.5%), the majority of S1 education complied with 15 respondents (33.3%). Based on the experience of 1-6 years, the majority were compliant with 36 respondents (80%), 7-12 years the majority were obedient, 4 respondents (8.9%). The conclusion of this research is that the minority DIII education is 5 respondents based on education, the minority 1-6 years experience is 5 respondents based on experience. Suggestions are expected for nurses who work in the health sector so that every action of postoperative wound care for Sectio Caesarea is in accordance with the established SOP